Bronchoscopy: the past, the present, and the future - Becker, Heinrich D. (Clinics in chest medicine, 2010)
This article discusses bronchoscopy: its history, including development of instruments and techniques and important historical figures; current techniques and issues; and future possibilities and potential controversies.
Gesehen am 21.12.2022